PELAKSANAAN TEKNIK SUPERVISI INDIVIDUAL SEBAGAI IMPLEMENTASI KERJA KEPALA SEKOLAH DI SMAN 2 PASAMAN - Ahmad Hosen (JURNAL MANAJEMEN PENDIDIKAN, 2017)
ABSTRACTBased on observations that have researchers do To teachers at SMAN 2 Pasaman, it was found that the competency of teachers remains low. The purpose of this study is to Improve Teacher competency as a working implementation of the principal at SMAN 2 Pasaman. This research is a school action. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 8 people Master SMA Negeri 2 Pasaman. Data were collected by using observation sheet. Data were analyzed using percentages.The results showed that Influence Learning Tool Workshop superintendent of schools can improve the competence of teachers at SMAN 2 Pasaman. This is evidenced by the increasing creativity of teachers from the first cycle to the second cycle. On average ability Creativity of teachers in the first cycle was 65.23 with less category and the second cycle is 83.88 with both categories. Keywords: individual supervision, implementation of work